Association of Ureaplasma infection pattern and azithromycin treatment effect with bronchopulmonary dysplasia in Ureaplasma positive infants: a cohort study - Xueyu Chen; Xuemei Huang; Yanqing Lin; Bingchun Lin; Chunyu Yang; Zhifeng Huang; Chuanzhong Yang (BMC Pulmonary Medicine, 2023)
Abstract Background It is unclear whether Ureaplasma-associated pneumonia and azithromycin treatment affect the risk for bronchopulmonary dysplasia (BPD). Methods A retrospective cohort study was performed in very low birth weight (VLBW) infants who tested positive for Ureaplasma within 72 h after birth in a tertiary unit. Chest X-ray (CXR) and laboratory test were performed before and after azithromycin treatment. Multivariate logistic regression analysis was used to identify the independent association between BPD and Ureaplasma-associated pneumonia, as well as BPD and effective azithromycin treatment. Results A total of 118 infants were included in the current study, of whom 36 developed BPD (defined as supplemental oxygen needed at postmenstrual age 36 weeks or discharge). The rate of BPD was significantly higher in infants with Ureaplasma-associated pneumonia (44.6%) compared to infants with Ureaplasma colonization (17.7%, P = 0.002). After adjusting for confounders, an effective azithromycin treatment was significantly associated with reduced risk of BPD [odd ratio (OR) 0.011; 95% confidence interval (CI): 0.000–0.250), whereas Ureaplasma-associated pneumonia was not significantly associated with BPD (OR 1.835; 95% CI: 0.548–6.147). Conclusion Effective Azithromycin treatment in Ureaplasma positive VLBW infants was associated with a reduced risk of BPD.